Judging victims : why we stigmatize survivors, and how they reclaim respect - Dunn, Jennifer L., 1957- (Boulder, Colo. : Lynne Rienner Publishers, 2012)
Dunn explores the shifting perceptions over time of victims as blameworthy, blameless, pathetic, or heroic figures. She also links those images to their real-world consequences, demonstrating that they dominate the ways in which people think about intimate violence and individual responsibility. Her analysis cuts to the core of fundamental issues at the center of debates about crime and deviance, victimization, and social problems.
Vocabularies of victimization: sympathy, agency, and identity -- Survivor movements then and now -- The anti-rape movement and blameworthy victims -- The battered women's movement and blameless victims -- Backlash and pathetic victims -- Survivors of clergy abuse and admirable victims -- Vanguard of victimology: survivors, identity work, and cultural change.
Originally published in hardcover, 2010.
Includes bibliographical references (p. 215-230) and index.
Keywords: Victims of crimes -- Psychology; Victims of crimes -- Public opinion; Victims of crimes -- Psychology; Victims of crimes -- Public opinion